Mutation profiling in gallbladder cancer in Indian population - Niraj Kumari; Christopher L Corless; Andrea Warrick; Carol Beadling; Dylan Nelson; Tanay Neff; Narendra Krishnani; Vinay Kumar Kapoor (Wolters Kluwer Medknow Publications, 2014)
Aim: Gallbladder cancer is an aggressive malignancy usually diagnosed at late stage. The molecular genetics of this cancer is heterogeneous and not well established. Mutation profiling of gallbladder cancer was performed through massarray technology with an aim to identify molecular markers involved in the tumor pathogenesis that can be helpful as markers for early diagnosis and targets for therapy. Materials and Methods: Forty nine cases of gallbladder cancer were screened through Sequenom Massarray technology for 390 mutations across 30 genes in formalin fixed paraffin embedded archived tissues and the results of mutation profiling was correlated with tumor characteristics. Mutations were observed in 9 of 49 cases across four genes - TP53 (four cases), CTNNB1 (two cases), PIK3CA (two cases), and KRAS (one case). Six of these cases were well differentiated but of eight of them belonged to stage II to IV disease. Six cases had associated gallstones. Conclusion: The mutation frequency found in gallbladder cancer is comparable to the data available in literature. Identification of PIK3CA and KRAS mutations would help in formulating more efficacious targeted approach for management. Studies with large number of cases would help in exploring more targets and better classification of these cancers at genetic level.